# SOLUTION: (square root 13 + square root z) (square root 13 - square root z)

Algebra ->  Algebra  -> Radicals -> SOLUTION: (square root 13 + square root z) (square root 13 - square root z)       Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Radicals -- complicated equations involving roots Solvers Lessons Answers archive Quiz In Depth

 Question 130155: (square root 13 + square root z) (square root 13 - square root z) Found 2 solutions by jim_thompson5910, stanbon:Answer by jim_thompson5910(28504)   (Show Source): You can put this solution on YOUR website!Throughout this problem, keep in mind that (remember you cannot take the square root of a negative number) Start with the given expression Foil the expression Combine the roots Cancel like terms Simplify Take the square root of to get 13. Take the square root of to get z. So simplifies to In other words, Answer by stanbon(57250)   (Show Source): You can put this solution on YOUR website!(square root 13 + square root z) (square root 13 - square root z) --------------- this follows the form (a+b)(a-b) = a^2-b^2 -------------- Your problem: = 13 -z ============== Cheers, Stan H.